Research on business oriented 5G base station energy saving system based on AI deep learning - Mengqiang XU (Dianxin kexue)
Due to the needs of 5G business development, the number of 5G base stations has increased, resulting in a sharp increase in the electricity cost of operators.Energy saving and consumption reduction has become the sustainable development demand of operators.Based on the research of mainstream 5G base station energy-saving mode and multi-directional 5G energy-saving scheme, a 5G base station energy-saving system based on a variety of AI algorithms was proposed.Through the high-precision service identification at the level of single SIM card, the best strategy of 5G base station flexible energy-saving was realized on the basis of ensuring the stable operation of 5G important services and other types of services.